Hollywood in China: How American Popular Culture Shapes Chinese Views of the "Beautiful Imperialist" – An Experimental Analysis. (28th October 2015) - Gries, Peter; Sanders, Matthew A.; Stroup, David R.; Cai, Huajian
Abstract: While most mainland Chinese today have extremely few direct contacts with either America or Americans, their indirect contacts with both, via globalized American popular culture, are increasing rapidly. Do daily parasocial contacts with American celebrities shape Chinese views of America? Based on two experimental studies, this paper argues that even indirect, subconscious exposure to American celebrities via popular magazine covers shapes Chinese views of America. However, the impact of that exposure depends upon both the specific nature of the bicultural exposure and the psychological predispositions of the Chinese involved. Not all Chinese are alike, and their personality differences shape whether they experience American popular culture as enriching or threatening, leading to integrative and exclusionary reactions, respectively. 摘要: 尽管绝大多数现代中国人从来没有和美国或美国人有过直接的接触, 但是, 在日益加剧的全球化的大背景下, 中国人接触美国流行文化的机会却无处不在。美国的流行文化会影响中国人对美国的看法吗? 本文以流行杂志封面的中、美明星人物为启动中、美, 结果发现, 大众杂志封面上的美国明星可以影响中国人对美国人的看法, 但是只有当美国明星人物出现在中国杂志封面上时, 这种影响才会发生。并且, 这种影响因人而异: 只有高民族自恋的人才会将美国流行文化看作威胁, 而低民族自恋的人却把美国流行文化视为有益, 并分别导致排斥性或包容性的反应。